Rancang Bangun Aplikasi Pengelolaan Aset pada PT. Bina Megah Indowood - Alfianto, Fatkur; Wulandari, Sri Hariani Eko; Santoso, Rudi (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
The development of information and communication technologies so rapidly and widely used in various fields of life, one of which industry and manufacturing, such as the accounting department is one of the activities is to manage the assets of the company. The use of information and communication technology in the industry is essential and needs to be prioritized, because it can improve the speed and accuracy in data processing and to support the accounting department in managing its assets. The activities in accounting department of PT. Bina Megah Indowood are managing asset data, maintenance of assets, changes in the status of assets, depreciation of assets, and acquisitions are still done manually and not centralized. It makes the accounting department have difficulty managing the data quickly and accurately. In addition, the asset data is not centralized accounting difficult to find valid data. To resolve the problems, it will be created an asset management application at PT. Bina Megah Indowood. With this new application, it is expected that the performance of the accounting department in asset management be the better and make it easier to manage and accelerate the assets reporting process.